Development and characterization of microsatellite markers for Lychnophora pinaster: a study for the conservation of a native medicinal plant - Haber, L. H. [UNESP]; Cavallari, M. M. [UNESP]; Santos, F. R. C.; Marques, Marcia Ortiz Mayo [UNESP]; Gimenes, M. A.; Zucchi, M. I. (Wiley-Blackwell Publishing, Inc, 2009)
Lychnophora pinaster Mart. (Asteraceae) is a Brazilian medicinal plant, extensively employed in popular medicine as an anti-inflammatory, analgesic and healing agent. Thirteen polymorphic microsatellite markers were developed and optimized for L. pinaster from an enriched genomic library. The markers were used to analyse 37 plants from two native populations, generating an average number of 6.6 alleles per polymorphic locus. These loci are important tools for future studies of population genetics.
Keywords: Lychnophora pinaster; diversity; native populations; primers; genetic structure; medicinal plant